1989
DOI: 10.1111/j.1365-2265.1989.tb01424.x
|View full text |Cite
|
Sign up to set email alerts
|

Methimazole‐induced Agranulocytosis in Japanese Patients With Graves’ Disease

Abstract: We reviewed the records of approximately 7000 Japanese patients whose hyperthyroidism was treated with methimazole (MMI) alone. Four patients (Group I) developed agranulocytosis during a second course of MMI therapy and eight patients (Group II) during an initial course. Six patients (three in each group) received less than 30 mg MMI daily. Agranulocytosis occurred after more than 2 months of therapy (12 weeks-1 year) in five patients. Seven patients were less than 40 years of age. One patient displayed a grad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
34
1

Year Published

1990
1990
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 10 publications
1
34
1
Order By: Relevance
“…Short-term complications of surgery included hematoma and transient vocal cord paralysis, transient hypothyroidism, and anesthesia-related death. Major complications of ATD therapy including agranulocytosis, hepatitis and vasculitis (9,29,30) occurred at both 7 weeks and 6 months after the start of therapy. They resulted in hospitalization, the discontinuation of ATDs, or death.…”
Section: Effectivenessmentioning
confidence: 99%
“…Short-term complications of surgery included hematoma and transient vocal cord paralysis, transient hypothyroidism, and anesthesia-related death. Major complications of ATD therapy including agranulocytosis, hepatitis and vasculitis (9,29,30) occurred at both 7 weeks and 6 months after the start of therapy. They resulted in hospitalization, the discontinuation of ATDs, or death.…”
Section: Effectivenessmentioning
confidence: 99%
“…The less uncommon side effect of the use of thyourea, even though very important, is agranulocytosis 1 . It may be present regardless of age, dose and treatment duration 8 , even though Meyer-Gebner et al have reported higher incidence with higher doses 6 . It has sudden onset and affects 0.2 to 0.3% of the patients 8,9 .…”
Section: Introductionmentioning
confidence: 93%
“…It may be present regardless of age, dose and treatment duration 8 , even though Meyer-Gebner et al have reported higher incidence with higher doses 6 . It has sudden onset and affects 0.2 to 0.3% of the patients 8,9 . Tamai et al, after a review of 7,000 patients with diagnosis of Basedow-Graves, found agranulocytosis in only 12 patients with incidence of 0.17% Based on this side effect, patients need to be instructed to stop medication and get in contact with their physician in case of fever or infection, especially of the oropharynx, considering that the clinical evidence of infections associated with the use of anti-thyroid drugs is usually symptomatic in this region 1,8,9 .…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…11 However, another study on a Japanese population found that the occurrence of ATD-induced agranulocytosis was not associated with dose, age and treatment duration. 12 Age, sex and type of ATD were not associated with any significant difference in the occurrence of agranulocytosis based on local data. 13 In 1990, granulocyte colony-stimulating factor, a recombinant human hematopoietic growth factor used to decrease infection associated with neutropenia caused by the myelosuppression from chemotherapy of cancer patients, was found to improve the ANCs of some patients with ATD-induced agranulocytosis.…”
Section: Introductionmentioning
confidence: 99%